World Statistics Pocketbook 1999 - United Nations Department of Economic; Social Affairs (United Nations, 1999)
This handy statistical pocketbook provides an easy-to-use international compilation of basic economic, social and environmental indicators for 208 countries and areas worldwide. It covers 57 key indicators in the areas of population, economic activity, agriculture, industry, energy, international trade, transport, communications, gender, education and environment, based on over 20 international statistical sources. The layout provides an easy-to-view comprehensive statistical profile of each country or area; and the notes on sources and definitions on indicators provide a valuable guide for further research. This issue of the World Statistics Pocketbook also shows comparative data for the years 1990 and 1999.